2020
DOI: 10.1016/j.clcc.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

High Concordance and Negative Prognostic Impact of RAS/BRAF/PIK3CA Mutations in Multiple Resected Colorectal Liver Metastases

Abstract: We investigated the intra-patient heterogeneity of driver gene mutations among colorectal liver metastases by sequencing 479 tumor samples from 106 patients. A near-perfect intra-patient concordance was found in the mutation status of the primary tumor and multiple metastatic lesions of KRAS/NRAS/BRAF and PIK3CA when high-sensitivity methods were applied. Mutations in KRAS alone and KRAS/NRAS/BRAF combined had a negative prognostic impact after liver resection. Background: The prevalence and clinical implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 52 publications
(68 reference statements)
1
29
0
Order By: Relevance
“…Intra-patient molecular heterogeneity is anticipated to have clinical implications (33), and current evidence in metastatic CRC suggests that heterogeneity on the DNA copy number level is more widespread than heterogeneity of single nucleotide variants (SNVs) and small insertions/deletions (indels), at least in cancer critical genes (21,23,24). We have shown that mutations in KRAS, NRAS, BRAF V600E (17), and TP53 are predominantly homogeneously present among multiple resected CRLM from each patient. The DNA copy number states of the four genes were more heterogeneous among metastases and correlated with the genome-wide inter-metastatic CNA heterogeneity, consistent with a lower selection pressure for these genes on the DNA copy number level than on the point mutation level.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Intra-patient molecular heterogeneity is anticipated to have clinical implications (33), and current evidence in metastatic CRC suggests that heterogeneity on the DNA copy number level is more widespread than heterogeneity of single nucleotide variants (SNVs) and small insertions/deletions (indels), at least in cancer critical genes (21,23,24). We have shown that mutations in KRAS, NRAS, BRAF V600E (17), and TP53 are predominantly homogeneously present among multiple resected CRLM from each patient. The DNA copy number states of the four genes were more heterogeneous among metastases and correlated with the genome-wide inter-metastatic CNA heterogeneity, consistent with a lower selection pressure for these genes on the DNA copy number level than on the point mutation level.…”
Section: Discussionmentioning
confidence: 84%
“…A total of 355 metastatic tumor samples from 103 patients have previously been analyzed for hotspot mutations in BRAF exon 15 and KRAS and NRAS exons 2-4 by Sanger sequencing (17). The remaining 86 tumor samples and 68 patients were analyzed in the present study.…”
Section: Mutation and Microsatellite Instability Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…CRLM commonly presents with multiple distinct liver lesions. Cancer-critical genes with a high mutation prevalence in CRC generally have a homogenous mutation pattern across metastatic lesions from the same patient [18,19], although treatment pressure may cause subclonal expansion, as illustrated by the emergence of resistant subclones with pre-existing or acquired KRAS mutations during anti-EGFR therapy [20,21]. More extensive mutation heterogeneity has been demonstrated in other protein-coding genes, both in intra-tumor and inter-tumor comparisons [22][23][24].…”
Section: Accepted Articlementioning
confidence: 99%